Effect Of Mineral Fertilizers On The Growth Period Of Ryjik Varieties - Abduazimov Akbar Mukhtorovich; Urinova Gulnora Ernazarovna; Kurbanaliev Fazliddin (Zien Journals, 2021)
A large amount of consumer oil is currently imported into the country from abroad, which in turn leads to high import prices. To provide the population with cheap and high-quality oil products, it is necessary to increase the cultivation of oilseeds in the country, to improve the technology for the production of oils and their introduction into production.
Keywords: introduction; consumer; currently imported; cheap